Force plate derived descriptive data for the countermovement jump, single leg countermovement, and countermovement rebound in elite female youth soccer players - Fahey, J. T.; Comfort, P.; Ripley, N. J. (The Journal of Strength and Conditioning Research, 2026)
This study was designed to compare phase-specific metrics for normative data for countermovement jump (CMJ), single leg countermovement jump (SLCMJ), and countermovement rebound jump (CMJ-R) in elite female youth soccer players across different ages. Ninety-four highly trained to elite female soccer players were categorized into 3 distinct phases: Foundation Development Phase (U11-U12, n = 21, 10.9 ± 0.6 years, 42.8 ± 7.6 kg, 148.6 ± 7.6 cm), Youth Development Phase (U13-U15, n = 35, 13.6 ± 1.0 years, 54.8 ± 7.9 kg, 160.6 ± 6.5 cm), and Professional Development Phase (U16-U21, n = 38, 16.2 ± 1.1 years, 63.4 ± 6.8 kg, 167.3 ± 5.8 cm) completed 3 CMJ, SLCMJ, and CMJ-R trials on force plates. A series of 1-way analysis of variance with pairwise comparisons and Hedge's g effect sizes (g) were performed to determine differences between phases. Jump height increased with age across all jumps (g = 0.14-1.34) with older players demonstrating a greater countermovement displacement and time to take-off to achieve higher relative net propulsive impulse. This information offers practitioners valuable insights into how age influences jump performance in female youth soccer players, enabling effective design of strength and conditioning programs to maximize jump performance.